Predicting successful hematopoietic stem cell collection in healthy allogeneic donors - Kayser, Sabine; Schlenk, Richard Friedrich; Steiner, Marcus; Klüter, Harald; Wuchter, Patrick (Transfusion medicine and hemotherapy, 2023)
Introduction: Collection of peripheral blood stem cells (PBSCs) from healthy donors is a well-established process. We aimed to identify factors predictive of successful CD34+ PBSC collection and established a formula capable of predicting CD34+ cell yield. Methods: We retrospectively evaluated 588 healthy adult donors (median age 29 years, range 18-69 years) at our institution from 2017 to 2022. The predicted minimal number of CD34+ cells was calculated as follows: (peripheral CD34+ cells/µL × adjusted collection efficiency of 30%) × total liters processed. This formula was further modified according to donor and recipient body weight (BW). Results: Median total collection was 8.0 × 106 CD34+ cells/kg BW (range 1.0-47.1 × 106 cells/kg BW) with 522 donors (89%) collecting ≥5.0 × 106 cells/kg of recipient BW. A second leukapheresis (LP) was performed in 49 donors. Need for two LPs was more common in female donors (OR 6.68, 95% CI, 2.62-17.05; p < 0.001), donors with higher age (OR for 10 years difference 1.53, 95% CI, 1.15-2.03, p = 0.003), donors with WBC count <30 × 109/L after 5 days of granulocyte-colony stimulating factor (G-CSF) stimulation (OR, 4.33; 95% CI, 1.59-11.83; p = 0.004), and a donor/recipient weight ratio <1 (OR 6.21, 95% CI, 2.69-14.34; p < 0.001). Predictive factors for optimal LP (i.e., ≥5.0 × 106 CD34+ cells/kg of recipient BW) were peripheral blood (PB) CD34+ cell count >50/µL (OR 12.82, range 6.34-25.92, p < 0.001), male donor (OR 2.77, range 1.06-7.23, p = 0.04), and a donor/recipient weight ratio >1 (OR 3.12, range 1.57-6.24, p = 0.001). WBC, platelets, hemoglobin, and age had no significant predictive value. Predicted versus observed number of CD34+ cells/kg BW collected demonstrated a very strong linear correlation (r = 0.925, 95% CI, 0.912-0.936, p < 0.0001). Conclusions: Of the routinely monitored indicators in PBSC donors, CD34+ cell count in PB is the most important factor in predicting G-CSF-induced PBSC yields. Higher age, female sex, WBC <30 × 109/L, and a donor/recipient weight ratio <1 are useful indicators for identifying suboptimal mobilizers. The modified formula has shown successful and consistent performance in the prediction of key outcome measures including the minimum CD34+ cell collection, determination of the required length of apheresis, and whether a second day of PBSC collection was necessary to achieve the respective collection goal.
Online veröffentlicht: 30. Juni, 2023
Gesehen am 02.11.2023